Characteristics of a Good Board of Directors for Indonesian SOEs Performance - Dian Kusuma Wardhani; Wiwik Supratiwi (Faculty of Economics and Business, Universitas Gadjah Mada, 2023)
Introduction/Main Objectives: This research aims to empirically show the positive influence of the board of directors' characteristics on company performance, proxied by female directors, political connections, economic and/or business educational backgrounds, and education levels. Background Problems: Essential characteristics are required to produce quality strategies because they directly affect the performance of SOEs, and Regulation PER-8/MBU/08/2020 of the Minister of SOEs restructures the BOD to increase the proportion of women. Novelty: This research measures SOEs' performance from their financial, administrative, and operational aspects. It comprehensively assesses the dual function of SOEs as public servants and producers of state profits. Research Methods: A total of 245 Indonesian state-owned enterprises were examined between 2014 and 2019 using panel regression with the random effect model. The companies’ performance data were obtained from the Information Management and Documentation Officer (PPID) of the Ministry of SOEs of the Republic of Indonesia (RI). Finding/ Results: The results show that female directors and political connections positively influence the performance of SOEs. According to the robustness test, directors with economic and/or business education backgrounds positively influence the financial performance, and the higher the education level is, this negatively influences the performance of SOEs. Conclusion: Essentially, this research supports the plan of the Minister of SOEs to increase the proportion of women on the boards of directors. The findings also prove that political connections strengthen the personal qualities of SOE directors, whether they are female or not.